Revitalizing sociology: urban life and mental illness between history and the present. (22nd February 2016) - Fitzgerald, Des; Rose, Nikolas; Singh, Ilina
Abstract: This paper proposes a re‐thinking of the relationship between sociology and the biological sciences. Tracing lines of connection between the history of sociology and the contemporary landscape of biology, the paper argues for a reconfiguration of this relationship beyond popular rhetorics of 'biologization' or 'medicalization'. At the heart of the paper is a claim that, today, there are some potent new frames for re‐imagining the traffic between sociological and biological research – even for 'revitalizing' the sociological enterprise as such. The paper threads this argument through one empirical case: the relationship between urban life and mental illness. In its first section, it shows how this relationship enlivened both early psychiatric epidemiology, and some forms of the new discipline of sociology; it then traces the historical division of these sciences, as the sociological investment in psychiatric questions waned, and 'the social' become marginalized within an increasingly 'biological' psychiatry. In its third section, however, the paper shows how this relationship has lately been revivified, but now by a nuanced epigenetic and neurobiological attention to the links between mental health and urban life. What role can sociology play here? In its final section, the paper shows how this older sociology, with its lively interest in the psychiatric and neurobiological vicissitudes of urban social life, can be our guide in helping to identify intersections between sociological and biological attention. With a new century now underway, the paper concludes by suggesting that the relationship between urban life and mental illness may prove a core testing‐ground for a 'revitalized' sociology.